Islam Today in Modern West: Fazlur Rahman’s and Tariq Ramadan’s Views on Jihad - Chusnul Chotimah Bimbo (Universitas Islam Negeri Mataram, 2019)
This paper discusses the issues of radicalism that have reappeared in the public sphere nowadays. The discussion will focus on the interpretation of Jihad by Fazlur Rahman and Tariq Ramadan. They are among two modern reformers whose ideas heavily focus on the social, economic and political issues about Muslims in the West. This paper will discuss the thoughts of these two figures about jihad spread across their various writings. As a contemporary reformist Muslim leader, Rahman and Ramadan had made many interpretations of the Qur'an by adapting to the social context of society when the interpretation was made, namely Western society. Their Qur'anic interpretations and their thoughts-whether directly or indirectly-reflect on the circumstances and challenges that Muslims encounter in the West, Europe and the US, today. This paper contributes to the discussion of the meaning of jihad and various attempts at interpretation of the term. Besides, this paper will at least provide an overview of how the face of Islam in the West in the modern era as it is today.